Greenhouse untuk Rakyat Gerakan Hijau dari, oleh, dan untuk Masyarakat - Irpan, Ade; Spalanzani, Widya; Widyantoro, Murwan; Mustakim, Indra (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
The greenhouse implementation program in RT 12 RW 035, Desa Bahagia, Babelan Subdistrict, aims to achieve green living through controlled-environment horticulture. This initiative focuses not only on local food security but also on organic waste management through composting and community education. Using a participatory approach, residents were directly involved in building and utilizing the greenhouse as both a productive facility and an environmental learning tool. The results indicate improved community understanding of waste management and the development of sustainable local economic potential. This program reflects the synergy of appropriate technology, community empowerment, and environmentally friendly living practices.